Assessment of Role of Hepcidin in Inflammatory Condition in Canine Pyometra - Leela, V.; Gogoi , Jayashree; Rajamanickam, K. (International Journal of Livestock Research, 2019)
Hepcidin is one of the great discovery in hematology, associated with iron homeostasis. It is a peptide of 25 amino acids and it is synthesized primarily in the liver, which has its synthesis linked to infections and inflammations. Pyometra is a common reproductive disorder in the middle-aged bitches in diestrual phase of estrous cycle when uterus is being exposed to high levels of progesterone. Pyometra is associated with bacterial infection leading to endometritis and toxaemia. Pyometra develops as a result of complex etiological factors which includes hormonal influence of uterine environment, virulence of the infecting bacteria with concomitant disability of the bitches to combat the infection or its inflammatory products. This accelerates the inflammatory process in the affected bitches and activates the macrophages to scavenge the pathogenic bacteria. The present study was conducted to explore the role of hepcidin hormone in mediating the inflammatory process in pyometra affected bitches. Blood samples were collected from ten dogs with open type of pyometra and from ten apparently healthy dogs. Haematological parameters and hepcidin were estimated in pyometra affected bitches and in control animals. Leucocytosis and neutrophilia and their blood hepcidin hormone level were elevated when compared to apparently healthy dogs. This shows that increase in hepcidin hormone is beneficial in mediating the inflammatory process because it increases the intracellular iron content of macrophages which is needed for destruction of engulfed pathogens.